REGRESSION MODELS TRANSVERSAL SIZES UPPER AND LOWER JAW AND DENTAL ARCH SAGITTAL CHARACTERISTICS IN BRACHYCEPHALIC GIRLS, DEPENDING ON THE CHARACTERISTICS OF CEPHALOMETRIC AND ODONTOMETRIC INDICATORS - А. V. Маrchenko (Bogomolets National Medical University, 2017)
The article presents described and analyzes regression mathematical models of transversal dimensions of the upper and lower jaw and sagittal characteristics of the dental arc, depending on the cephalometric and odontometric characteristics of brachycephalic girls with orthognathic bite. Of the 18 possible linear sizes needed to construct the correct form of the dental arc in brachycephalic girls with orthognathic bite, all 18 reliable models (determination coefficient from 0.803 to 0.934) were constructed, depending on the odontometric and cephalometric characteristics. Constructed models with a determination coefficient more than 0.6 more often include the size of teeth (72.3%, of which 20.5% accounted for the upper incisors, 20.5% for the lower incisors, 4.5% for the upper canine, 11,6% - on the canine, 5,4% - on the upper small corner teeth, 8,0% - on the lower small corner teeth, 1,8% - on the upper first large angular teeth) than the cephalometric indices (27,7 %). Among the sizes of upper and lower incisors, canines, small and first large angular teeth models most often include the following indicators: mesiodistal dimensions of crowns of teeth (17,9%, of which 10,7% on the upper jaw); length of teeth (13.4%, of which 5.4% on the upper jaw); the width of the dentin-enamel border in the mesiodistal direction (11.6%, of which 5.4% in the upper jaw); vestibule-tongue sizes crowns of teeth (10.7%, of which 4.5% on the upper jaw). Among the cephalometric indices models most commonly included intra-orbital width (3.6%)